Perbedaan Prestasi Belajar Antara Siswa yang MenderitaGondok yan Tidak Menderita Gondok di SDN Gonggang 4Kecamatan Poncol Kabupaten Magetan - Nugroho, Adhika Kustantyo; , Abi Muhlisin, SKM, M.Kep; , Nunuk Haryatun, S.Kep., Ns (2013)
The Standardization of students' achievement is how students can follow the learning process in class and it is counted through the score in the student's report book. Students who have high concentration in the learning process can increase their achievement. Yet the achievement can be disrupted when student is suffering some disease like goiter. This fact also occurs to the students from grade 1 until grade 6. There are some student who suffer goiter and some others are not. The aim of this research is to find out the difference of student achievement between students suffering Goiter and students who do not suffer Goiter in Gonggang 4 Primary School in Poncol, Magetan County. The research method conducted by the researcher is analytical survey. The research uses Cross Sectional design. The research sample is 40 students from all grades of Gonggang 4 Primary School. The sample is divided into two groups, 20 students who suffer goiter and 20 students who do not suffer goiter. The instrument of the research is goiter check-up palpasily and students' achievement through the report book. The data, then, are tested statistically using Mann Whitney Compative Test. The result of the research shows the average score of students suffering goiter is 74.06 and the average score of students who do not suffer goiter is 79.14. From the data taken from the students who suffer goiter, 7 respondents (35%) reach high achievement, and 13 students (65%) get low score. From the uninfected students, 17 respondents (85%) reach high achievement, and 3 students (15%) get low score. The Z score of Mann Whitney Test is 2.086 with p=0.037 (p<0.05). From the result, the hypothesis taken is rejected Ho. It means that there is difference of student achievement between students suffering Goiter and students who do not suffer Goiter in Gonggang 4 Primary School in Poncol, Magetan County.